Exploratory analysis of high-dose corticosteroid therapy on epileptic encephalopathy with spike-and-wave activation in sleep - Xiaoyue, Hu; Hongwei, Tang; Jianbiao, Wang; Jingbo, Ma; Ying, Hua (Frontiers in Pediatrics, 2024)
Objective: This study aims to evaluate the therapeutic efficacy of highdose corticosteroid therapy in children diagnosed with epileptic encephalopathy with spike-and-wave activation in sleep (EE-SWAS), investigate associated clinical indicators influencing treatment outcomes, and establish a predictive model for recurrence.Children diagnosed with EE-SWAS who received high-dose corticosteroid therapy were categorized into responder group and nonresponder group. Data on clinical parameters, electroencephalogram (EEG) features, and serum cytokine levels were collected. Six months post-treatment, the effectively treated children were further stratified into recurrence and non-recurrence groups. Risk factors for poor outcomes following corticosteroid therapy were identified using univariate analysis.Multivariate logistic regression analysis was then employed to determine independent factors influencing the recurrence of corticosteroid therapy, which facilitated the development of a predictive model.Results：The study included 48 children, with 33 cases in the responder group (effective rate=68.8%) and 15 cases in the non-responder group.The responder group exhibited an older onset age of electrical status epilepticus in sleep (ESES) and higher proportions of combined benzodiazepines (BZDs) use (P<0.05). Among those responding to corticosteroid therapy, 11 cases experienced a recurrence (recurrence rate=33.3%), while 22 cases did not. Significant differences were observed between the two groups concerning age of seizure onset, age of ESES onset, seizure frequency, atypical presentations, and concomitant frontal lobe discharges (all P<0.05). Concomitant frontal lobe discharges and an earlier age of seizure onset were identified as risk factors for ESES recurrence following corticosteroid therapy. The predictive model was formulated as Logit(P) = 2.35 × presence of frontal lobe discharges -0.802 × age of seizure onset + 2.457. The Area Under the Curve (AUC) of Receiver Operating Characteristics (ROC) was 0.93, with sensitivity and specificity at 100% and 77.3%, respectively.High-dose corticosteroid therapy for EE-SWAS exhibited a high effective rate as well as a notable recurrence rate. Onset age of ESES and combined benzodiazepines usage correlated with therapeutic efficacy.Seizure onset age and the presence of frontal lobe discharges may hold predictive value for recurrence following corticosteroid therapy.